STUDY DETERMINATION OF AREA DESIGN OF DOMESTIC WASTE WATER IN THE REGIONAL SQUARE AREA OF KOTO TANGAH PADANG CITY - Riyanto, Sugeng; Razak, Abdul; Dewata, Indang (Preventif: Jurnal Kesehatan Masyarakat, 2017)
Background & Objective: Management of domestic wastewater to improve access of domestic wastewater services that are environmentally friendly, so as to achieve improved quality of life of society and a better and healthier environment. This study aims to assess the risky areas of residential areas to improve access and management of domestic waste water in districts Koto Tangah Padang City. Material and Method: This research use cross sectional design. Population and sample of 520 families. Analysis of data used univariate and bivariate. Results: The results of this study indicate that 8.74% of the non-accessed latrines are categorized as having single defecation, 20% have no septic tanks, access to the lowest stool treatment system in Kelurahan Koto Pulai, Batipuh Panjang and Padang Sarai at 37, 5%. 76.95% safe access to latrines and no secure access in Kelurahan Balai Gadang.Penentuan wastewater area of domestic wastewater sanitation of domestic wastewater components in Kecamatan Koto Tangah Kota Padangyang included in the level of very high risk (risk 4) consists of Kelurahan Balai Gadang. Correlation test (p = 0.001) indicate a significant relationship between education and community income with the support of Jamban and SPALD ownership in districts Koto Tangah Padang City. Conclusion: It is necessary to increase the welfare of the program that touches directly to the rising public which has implications for the improvement of domestic sewage treatment system facilities